Domestic violence in Latvia: assessment of compliance with international and regional standards - Skadmane, Amanda (Riga Graduate School of Law, 2024)
Domestic violence is a concerning issue globally and in Latvia. The problem is not only widely dispersed geographically, but its occurrence is widespread and seriously affects physical and mental health well-being. The centuries-old belief that women are inferior to men has created integrated problems related to gender inequality and led to existing social attitudes towards domestic violence. The thesis's main focus is on whether Latvian domestic legislation effectively addresses domestic violence and complies with regional and international legal instruments. The examination of Latvian domestic legislation revealed a flaw in the Latvian legal system which is the lack of a uniform definition of domestic violence. Moreover, it concluded that if a state has various mechanisms in place to protect victims of domestic violence, they need to be enforced properly. Since it can be observed from the European Court of Human Rights case law, it is apparent that states need to do everything in their power to protect victims from domestic violence.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Comparative law; Research Subject Categories::LAW/JURISPRUDENCE::Criminal law; domestic violence; Latvia; CEDAW; Istanbul Convention; European Court of Human Rights